2011
DOI: 10.1001/jama.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cell Phone Radiofrequency Signal Exposure on Brain Glucose Metabolism

Abstract: Context The dramatic increase in use of cellular telephones has generated concern about possible negative effects of radiofrequency signals delivered to the brain. However, whether acute cell phone exposure affects the human brain is unclear. Objective To evaluate if acute cell phone exposure affects brain glucose metabolism, a marker of brain activity. Design, Setting, and Participants Randomized crossover study conducted between January 1 and December 31, 2009, at a single US laboratory among 47 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
148
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(162 citation statements)
references
References 36 publications
6
148
0
8
Order By: Relevance
“…Exposure to RF from phones is localized and therefore, if a risk exists it is likely to be greatest for tumors in regions with greatest energy absorption (Cardis et al, 2008) A recently published study (Volkow et al, 2011) demonstrated that while using a mobile phone, brain metabolism was increased in the orbito-frontal cortex and the temporal pole areas of the brain, areas that are close to where phone's antenna meets the head. Authors concluded, "This finding is of unknown clinical significance".…”
Section: Mobile Phone Penetrationmentioning
confidence: 99%
“…Exposure to RF from phones is localized and therefore, if a risk exists it is likely to be greatest for tumors in regions with greatest energy absorption (Cardis et al, 2008) A recently published study (Volkow et al, 2011) demonstrated that while using a mobile phone, brain metabolism was increased in the orbito-frontal cortex and the temporal pole areas of the brain, areas that are close to where phone's antenna meets the head. Authors concluded, "This finding is of unknown clinical significance".…”
Section: Mobile Phone Penetrationmentioning
confidence: 99%
“…Recently, in a controlled experiment with healthy participants, researchers with the US National Institutes of Health reported observing increased brain glucose metabolism in the region closest to the cell phone antenna when the device was in operation. If confirmed by other studies, this would imply that there may be a biological, nonthermal effect from cell phones (12). Institutions such as the World Health Organization and the National Academy of Sciences have specifically advocated for increased research efforts into the possible health effects from cell phones and other new sources of exposure to radiofrequency fields especially for children and fetuses (13,14).…”
mentioning
confidence: 97%
“…According to the WHO's International Agency for Research on Cancer (IARC), RF-EMR fields have been classified as possibly carcinogenic to humans on the basis of an increased risk for brain glioma that some studies have associated with the use of wireless phones [1]. A recent study [2] provided evidence that the human brain is sensitive to the effects of RF-EMR from acute cell phone exposure. The findings of increased metabolism in regions closest to the antenna during acute cell phone exposure suggest that brain absorption of RF-EMR may enhance the excitability of brain tissue.…”
mentioning
confidence: 99%